(untitled) (Journal of Bangladesh Institute of Planners, 2012)
The universal complaint that the Urban Local Bodies (ULBs) i.e. City Corporations and Municipalities (Pourashavas in Bangladesh) in developing countries are in dire need of resources not only for investment to meet the increasing demand of growing urban population but also for maintenance of the existing services. Municipal finance in Bangladesh has so far not been extensively studied. For this research, Dhaka City Corporation (DCC) has been chosen for a case study. The research has investigated on how the financial capability of City Corporation can be strengthened. Investigation was made on various sources of revenue, existing state of tax base, and various problems pertaining to income and expenditure of Dhaka City Corporation. The study has explored potential sources of financing and made some suggestions to enhance local initiatives in strengthening financial capability. DOI: http://dx.doi.org/10.3329/jbip.v2i0.9574 Journal of Bangladesh Institute of Planners Vol. 2, December 2009, pp. 136-144